Analisis Nilai Tambah Produk Aren di Kecamatan Lareh Sago Halaban Kabupaten Lima Puluh Kota - Hanum, Latifa; Sari, Regia Indah Kemala; Fitrianti, Siska; Hendriani, Riva (Politeknik Pertanian Negeri Payakumbuh, 2021)
Lareh Sago Halaban sub-district is one of the largest Aren producers in Lima Puluh Kota Regency; however, it is famous as Nagari Tuak which sells Aren to produce palm wine. Palm sugar processing is generally carried out into molded sugar, while granulated palm sugar is still limited. This study aimed to analyze the added value of palm sugar products in Lareh Sago Halaban sub-district by comparing the added value of molded sugar with granulated palm sugar products. The research area was determined purposively, 30 molded palm sugar processors and five granulated palm sugar processors as respondents. The study was conducted in November-December 2020. The data were processed using the Hayami method. The added value of molded palm sugar is IDR 960 (the add-value ratio is 26percents), and the added value of granulated palm sugar is IDR 2.452 (the add-value ratio is 46percents). The added value of granulated palm sugar is in the high category (greater than 40percents) and molded sugar is in the medium category (15-40percents). The highest percentage of owner compensation factor of production for molded palm sugar is received by workers (44percents), meanwhile, for granulated palm sugar is obtained by owners of capital (processors if owned by themselves) is percents.